Socioeconomic development and human well-being: seasonal survey on nutrition: third round - Khatun, Masuma; Tarannum, Sabah; Rasheed, Sabrina; Hyder, S.M. Ziauddin (BRAC Research and Evaluation Division (RED), 2019)
Since 1992, BRAC and ICDDR,B have been implementing a joint research project in Matlab, Bangladesh to assess the pathways of impact of BRAC's development interventions on human well-being. The project identified improved nutritional status as one of the components of human wen-being. This report documents the nutrition component of the third round seasonal survey findings conducted during January to May 1996 using the four-cell survey design. A total of 2076 households were interviewed to connect data on household food security and on anthropometry. Data on preceding one week's household food inflow and outflow were connected to describe food security at the household level. The anthropometric survey was conducted for an household members aged 6 month and above. Data on different parameters are shown in the report stratified by BRAC member, BRAC eligible non~member and BRAC non eligible non-member.